Chinese students studying in American high schools: international sojourning as a pathway to global citizenship. Issue 5 (3rd September 2019) - Cheng, Baoyan; Yang, Po
ABSTRACT: Using global citizenship as the framework and guided by a phenomenological approach, this paper examines the experiences of overseas education on Chinese students studying in American high schools, and the mechanisms through which potential growth takes place. The data were collected from interviews with 15 Chinese students studying at American high schools and seven teacher participants who work closely with them. Findings reveal that international sojourning could potentially serve as an effective pathway to global citizenship because it may help international students develop global competencies (knowledge, understanding and skills), and global consciousness (values and attitudes). The paper argues that the process of growing into a global citizen may be viewed as an advanced level of student development, and the mechanisms through which this kind of ideal transformation takes place which were identified in this study include: having non-vanity motives, developing self-authorship, exposure to different perspectives, and experiencing disadvantages and deprivation.